Prevalence of antibiotic-resistant Acinetobacter baumannii in a 1000-bed tertiary care hospital in Tehran, Iran - Rahbar Mohammad; Mehrgan Hadi; Aliakbari Negar (Wolters Kluwer Medknow Publications, 2010)
Acinetobacter baumannii is a ubiquitous pathogen that has emerged as a major cause of healthcare-associated infections. Acinetobacter baumannii usually causes respiratory tract, urinary tract, blood stream and surgical site infections. They are of increasing importance because of its ability to rapidly develop resistance to the major groups of antibiotics. There are few data available on the antimicrobial susceptibility of A. baumannii in Iran. During the period of study from July 2005 to November 2006, a total of 88 strains of A. baumannii were isolated from clinical specimens obtained from patients hospitalized in an Iranian 1000-bed tertiary care hospital. Conventional bacteriological methods were used for identification of A. baumannii. Susceptibility testing was performed by the method recommended by Clinical Laboratory and Standards Institute (CLSI). The majority of isolates were from respiratory tract specimens. The organism showed high rate of resistance to ceftriaxone (90.9%), piperacillin (90.9%), ceftazidime (84.1%), amikacin (85.2%) and ciprofloxacin (90.9%). Imipenem was the most effective antibiotic against A. baumannii and the rate of resistance for imipenem was 4.5%. The second most effective antibiotic was tobramycin, and 44.3% of A. baumannii isolates were resistant to this antibiotic. In conclusion, our study showed that the rate of resistance in A. baumannii to imipenem was low. There was a significant relationship between demographic features of patients such as age, undergoing mechanical ventilation, length of hospital stay and drug resistance.